M & A : a practical guide to doing the deal - Hooke, Jeffrey C. (Wiley finance series., 2015)
"The comprehensive M&A guide, updated to reflect the latest changes in the M&A environmentM&A provides a practical primer on mergers and acquisitions for corporate executives and anyone involved in the deal. Its comprehensive approach covers each step in the process, from finding an opportunity, to analyzing the potential, to closing the deal, with new coverage of private equity funds and international transactions. This updated second edition also includes information on emerging markets, natural resource valuation, hostile takeovers, special deals, and more, plus new examples and anecdotes taken from more current events. Additional illustrations and charts help readers quickly grasp the complex information, providing a complete reference easily accessible by anyone involved in M&A.The mergers and acquisitions environment has changed in the thirteen years since M&A was initially published, creating a tremendous need for authoritative M&A guidance from a banker's perspective. This M&A update fills that need by providing the characteristic expert guidance in clear, concise language, complete with the most up-to-date information. Discover where M&A fits into different corporate growth strategies, and the unique merits it confers Delineate clear metrics for determining risk, valuation, and optimal size of potential acquisitions Gain deeper insight into the fundamentals of negotiation, due diligence, and structuring Understand the best time to sell, the best way to sell, and the process of the sale itself In the past decade, the dollar value of M&A deals has jumped ten-fold, and the number of individuals involved has expanded considerably. More and more executives, analysts, and bankers need to get up-to-date on the mechanics of M&A, without wading through volume after volume of dense, legalistic jargon. Finally, M&A is back - providing a complete reference to the current state of the M&A environment"--